Improved Dissolution of Albendazole from High Drug Loaded Ternary Solid Dispersion: Formulation and Characterization - Halder, Shimul; Azad, MAK; Iqbal, Hrishik; Shuma, Madhabi Lata; Kabir, Eva Rahman (Dhaka University Journal of Pharmaceutical Sciences, 2021)
Bioavailability of a poorly water-soluble drug, e.g., widely used anthelmintic drug Albendazole (ABZ), is very low and thus, to obtain an optimized therapeutic efficacy, the aqueous solubility of such drugs needs to be enhanced. The objective of this study was to develop an effective high drug-loaded solid dispersion (SD) of ABZ with two biocompatible drug carriers, namely Soluplus® and Ludiflash® to improve its physicochemical characteristics. Equilibrium solubility study was performed to choose the optimum polymer ratio among the formulations and it showed up to 50-fold enhanced solubility compared to crystalline ABZ in water. X-Ray Powder Diffraction (XRPD) and Differential Scanning Calorimetry (DSC) studies of SD-ABZ showed reduced crystallinity of ABZ in the SD. The polymeric carriers, notably Soluplus®, are thought to play a key role in the reduction of crystallinity and molecular polydispersity of ABZ. The dissolution studies in water showed improved dissolution of SD-ABZ compared to crystalline ABZ, with a quick onset of drug release followed by gradual dissolution. However, due to high drug-loading and retention of crystalline ABZ in the sample, the dissolution behavior was not as expected, and may require further studies to optimize the SD-ABZ formulation. Dhaka Univ. J. Pharm. Sci. 20(2): 149-158, 2021 (December)